Chemical ordering beyond the superstructure in long-range ordered systems. (29th November 2016) - Stana, Markus; Sepiol, Bogdan; Kozubski, Rafał; Leitner, Michael
Abstract: To describe chemical ordering in solid solutions systems Warren–Cowley short-range parameters are ordinarily used. However, they are not directly suited for application to long-range ordered systems, as they do not converge to zero for large separations. In this paper, the theory is generalized to long-range ordered systems and chemical short-range order beyond the superstructure arrangements is discussed quantitatively on the example of a non-stoichiometric B2-ordered intermetallic alloy. Parameters of interatomic potentials are taken from an embedded atom method calculations and the degree of order is simulated by the Monte Carlo method. Both on-lattice and off-lattice methods, where the latter allows individual atoms to deviate from their regular lattice sites, were used, and the resulting effects are discussed.